Актуальные проблемы преподавания украинского языка как иностранного - Абрамова, И. Г.; Abramova, I. G.; Абрамова, Інна Георгіївна (Минск : БГУ, 2021)
В статье рассмотрены актуальные проблемы преподавания украинского языка иностранным студентам. Подано традиционные и инновационные подходы к изуче- нию украинского языка инокоммуникантами в высшем медицинском чреждении. До- казано, что аудирование является одним из ключевых видов речевой деятельности в системе лингвистической подготовки иностранцев. The article considers topical problems of teaching Ukrainian to foreign students. Traditional and innovative approaches to the study of the Ukrainian language by foreign communicators in a higher medical institution are presented. It is proved that listening is one of the key types of speech activity in the system of linguistic training of foreigners.
Actual problems of teaching the ukrainian language as a foreign
Keywords: коммуникация; инокоммуниканты; аудирование; мотивация; билингвизм; communication; foreign communicators; listening; motivation; bilingualism